UV-C Technology to Support Air Quality For Safety Work and Security From Biological Agent Threats - Lilik Mugiharto; Aries Sudiarso; Luhut Simbolon; Suparlan Suparlan; Wely Pasadena (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: The UV-C-based air disinfection device is the equipment used for air disinfection whose working principle uses UV-C radiation to inactivate microorganisms. This study aimed to determine the effectiveness of UV-C devices for disinfection in the indoor air at the workspace and the safety of humans in the room from being exposed to UV-C radiation when the disinfectant is operating. The research used quantitative methods through laboratory experiments. The working principle of the UV-C device is to circulate air in the room through a chamber equipped with a UV-C radiation source from an electric lamp with a wavelength of 254 nm. Laboratory tests were carried out with the Total Plate Count (TPC) parameter to determine its effectiveness by measuring the number of conditions before and after treatment. The average effectiveness value at 30 minutes was 64.14% and at 60 minutes it was 86.26%, so the effect increased with time. In terms of the dangers of UV-C radiation, UV-C devices are safe to use with designs and engineering that can prevent or minimize UV-C radiation outside the device. The radiation in human skin is not beyond the specified allowed. The result of measuring UV-C radiation in the workspace was 0.000 μW/cm2. UV-C technology can be used as a defense tool against biological agents effectively and safely.Abstrak: Perangkat disinfeksi udara berbasis UV-C merupakan alat yang digunakan untuk disinfeksi udara yang prinsip kerjanya menggunakan radiasi sinar UV-C untuk menonaktifkan mikro organisme. Tujuan penelitian ini adalah menentukan efektifitas perangkat UV-C pada disinfeksi mikroorganisme di udara dalam ruang kerja dan menentukan keamanan terhadap manusia yang berada di dalam ruangan dari paparan radiasi sinar UV-C pada saat disinfektor beroperasi. Prinsip kerja perangkat UV-C adalah mensirkulasikan udara pada ruangan untuk melalui chamber yang telah dilengkapi dengan sumber radiasi UV-C yang berasal dari lampu elektrik dengan panjang gelombang 254 nm. Dilakukan uji laboratorium dengan parameter Total Plate Count (TPC) untuk mengetahui efektifitasnya dengan mengukur jumlah kondisi sebelum dan sesudah sehingga diperoleh nilai rata-rata efektifitas pada 30 menit adalah 64,14% dan 60 menit adalah 86,26% sehingga efektifitas naik dengan ditambahnya waktu. Perangkat UV-C dari segi bahaya radiasi UV-C aman digunakan dengan desain yang dapat mencegah/meminimalisir radiasi UV-C sehingga tidak sampai pada kulit manusia melebihi nilai ambang batas yang ditentukan. Hasil ukur radiasi UV-C di ruang kerja adalah 0,000 μW/cm2. Teknologi UV-C dapat digunakan sebagai alat pertahanan terhadap agensia biologi dengan efektif dan aman.